2012
DOI: 10.1016/j.devcel.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A Gβγ Effector, ElmoE, Transduces GPCR Signaling to the Actin Network during Chemotaxis

Abstract: Activation of G protein-coupled receptors (GPCRs) leads to the dissociation of heterotrimeric G-proteins into Gα and Gβγ subunits, which go on to regulate various effectors involved in a panoply of cellular responses. During chemotaxis, Gβγ subunits regulate actin assembly and migration, but the protein(s) linking Gβγ to the actin cytoskeleton remains unknown. Here, we identified a Gβγ effector, ElmoE in Dictyostelium, and demonstrated that it is required for GPCR-mediated chemotaxis. Remarkably, ElmoE associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 53 publications
2
74
0
2
Order By: Relevance
“…S1A). Mass spectrometry (MS) analysis revealed that p40 and p9 were Gα4 and Gγ, respectively; p240 was ElmoE, which is a known Gβ-binding protein (18); and p30 was a previously uncharacterized protein encoded by DDB_G0271086 and designated as Gip1. Gip1 contained a pleckstrin homology (PH) domain at the N terminus between amino acids 1-109 and an unidentified region at the C terminus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A). Mass spectrometry (MS) analysis revealed that p40 and p9 were Gα4 and Gγ, respectively; p240 was ElmoE, which is a known Gβ-binding protein (18); and p30 was a previously uncharacterized protein encoded by DDB_G0271086 and designated as Gip1. Gip1 contained a pleckstrin homology (PH) domain at the N terminus between amino acids 1-109 and an unidentified region at the C terminus.…”
Section: Resultsmentioning
confidence: 99%
“…1A). ElmoE associates with Gβγ and serves as a guanine nucleotide exchange factor for Rac to control F-actin in pseudopods (18). Because the interaction between G proteins and ElmoE was unaffected in gip1Δ cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the asymmetric distribution of PIP3 is no longer considered to be the immediate signal responsible for directing actin polymerization in moving cells. Recently, a complex of Elmo/Dock proteins was shown to directly link the G bg component of Dictyostelium chemoattractant receptors to Rac activation of the actin cytoskeleton during chemotaxis [55]. Lockley et al [56] were able to reduce the Meinhardt model described earlier to two variables and to fit it to experimental data of randomly migrating Dictyostelium cells, and cells orienting in a gradient of mechanical shear flow.…”
Section: Actin Polymerization In Response To Extracellular Signalsmentioning
confidence: 99%
“…During chemotaxis, Gβγ subunits regulate actin assembly and migration, but the protein(s) linking Gβγ to the actin cytoskeleton remains unknown. The Gβγ effector, ElmoE in Dictyostelium, had demonstrated that it is required for GPCR-mediated chemotaxis [54]. As ElmoE associates with Gβγ and Dock-like proteins to activate the small GTPaseRac, in a GPCR-dependent manner, and also associates with Arp2/3 complex and F-actin, ElmoE serves as a link between chemoattractant GPCRs, G-proteins and the actin cytoskeleton.…”
Section: Anaphylatoxins Receptorsmentioning
confidence: 99%
“…As ElmoE associates with Gβγ and Dock-like proteins to activate the small GTPaseRac, in a GPCR-dependent manner, and also associates with Arp2/3 complex and F-actin, ElmoE serves as a link between chemoattractant GPCRs, G-proteins and the actin cytoskeleton. The pathway, consisting of GPCR, Gβγ, Elmo/Dock, Rac, and Arp2/3, spatially guides the growth of dendritic actin networks in pseudopods of eukaryotic cells during chemotaxis [54].…”
Section: Anaphylatoxins Receptorsmentioning
confidence: 99%